Current patterns of care for patients with extensive stage small cell lung cancer: Survey of US radiation oncologists on their recommendations regarding thoracic consolidation radiotherapy. (October 2016) - Mitin, Timur; Jain, Aditya; Degnin, Catherine; Chen, Yiyi; Henderson, Mark; Thomas, Charles R.
Highlights: Thoracic consolidation RT for ES-SCLC is recommended by most US radiation oncologists. There is a high degree of variability in patient selection and recommended RT doses. Respondents with high knowledge of published data recommend lower RT doses. Abstract: Objectives: Current National Comprehensive Cancer Network (NCCN) guidelines recommend thoracic consolidation radiation therapy (TCRT) for patients with Extensive Stage Small Cell Lung Cancer (ES-SCLC) with response to systemic chemotherapy, based on two randomized clinical trials, which varied in patient selection and radiation therapy doses administered. The current pattern of practice among US radiation oncologists is unknown. Materials and methods: We have surveyed practicing US radiation oncologist via a short online questionnaire. Respondents' characteristics and their self-rated knowledge base were analyzed for association with their treatment recommendations. Results: We received 473 responses from practicing US radiation oncologists. Over half of respondents were practicing for over 10 years after completing residency training and 70% treated more than 10 lung cancer patients per year. 96% of respondents recommend TCRT for patients with ES-SCLC after systemic chemotherapy. Patient selection and radiation therapy doses vary greatly. High self-rated knowledge of individual clinical trials is associated with lower TCRT recommended doses. Patients treated at academic centers are less likely to receive TCRT than patients treated in private clinics (p = 0.0101). Conclusion: Our analysis revealed that among the respondents, there was a very high adherence to current NCCN guidelines, which recommend TCRT for ES-SCLC patients with clinical response to systemic chemotherapy. The great variability in patient selection and radiation therapy doses is concerning and calls for future clinical trials to standardize treatment approaches and improve treatment outcomes among patients with ES-SCLC. Until such data exists and in light of poor long-term survival of patients with ES-SCLC, the shorter and less toxic regimen of 30 Gy in 10 fractions should be used as the standard of care and the more aggressive regimens studied on clinical protocols.